2016
DOI: 10.1016/j.jfoodeng.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sunflower and rapeseed lecithin on the rheological properties of spreadable cocoa cream

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
2
20
3
Order By: Relevance
“…The higher oil/fat content and the lower milk/whey powder content may also be caused to weak network between particles. The highest Casson yield stress and the lowest Casson viscosity was observed for Sample C. Similar findings was observed for spreadable cacao cream samples (Lončarević et al, ). In general, rheological parameters of chestnut creams were affected by oil/fat and milk/whey powder contents.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The higher oil/fat content and the lower milk/whey powder content may also be caused to weak network between particles. The highest Casson yield stress and the lowest Casson viscosity was observed for Sample C. Similar findings was observed for spreadable cacao cream samples (Lončarević et al, ). In general, rheological parameters of chestnut creams were affected by oil/fat and milk/whey powder contents.…”
Section: Resultssupporting
confidence: 84%
“…The parameter D (90) showed that 90% of the volume distribution of all the samples was finer than 247 μm. This value was higher than those of Lončarević et al () in cocoa cream and Lima et al () in peanut butter . It was noteworthy that all of the PSD parameters showed significant negative correlation with σ 0 ( p < .05).…”
Section: Resultscontrasting
confidence: 67%
“…(), the effects of substitution of skim milk powder with soy flour and refining time on the particle size and rheological properties of compound chocolate were investigated. The rheological properties of spreadable cocoa cream prepared by a ball mill and containing lecithin extracted from different origins (sunflower, rapeseed and soy lecithin) have also been investigated (Loncarevic et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Some studies dealing with milk chocolate (Franke et al, 2002;Lucisano et al, 2006;Zaric et al, 2012Zaric et al, , 2015Zaric et al, , 2016Bolenz & Manske, 2013;Pajin et al, 2013and Bolenz et al, 2014a, 2014b, dark chocolate (Alamprese et al, 2007) and chocolate spreads (Petkovic et al, 2013;Loncarevic et al, 2015) produced by ball mills have been conducted by several researchers. However, there are scarce studies about using ball milling and optimisation of parameters for compound chocolate production, thus necessitating such a study to gain understanding and optimise quality and also costs.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike chocolate, spreadable cocoa cream products do not contain cocoa butter, but contain cheaper vegetable fats and may also contain vegetable oil to improve spreadability of final product (Lončarević et al . ).…”
Section: Introductionmentioning
confidence: 97%